Global Trends in Sharia Audit Practice: An In-depth Bibliometric Exploration - Syaputri, Anastasya Dinda; Sigid, Sigid Eko Pramono (Review on Islamic Accounting, 2024)
The surge in publications focused on Sharia Audit Practice from 2011 to 2023 has been comprehensively explored through bibliometric analysis on the Dimension.ai platform. The research aims to identify prevalent topics and writing styles among authors in this sector. Using the search term "Sharia Audit Practice" on December 7, 2023, numerous contributions have significantly enhanced the field's research output. A prominent work, "Shariah Auditing: Analyzing the past to prepare for the future," delves into the current impact of Sharia Audit Practice. Noteworthy themes like "Sharia Governance," "Sharia Committee," and "Sharia Compliance" underscore its importance and prevalence in related discussions. The study showcases prolific authors and examines current trends, providing valuable insights for future academic and professional endeavors in this field. Recommendations include addressing awareness challenges, establishing supportive regulatory frameworks, and promoting sustainable research initiatives for the ongoing development of Sharia Audit Practice research.